SCALE STRUCTURE OF FRESHWATER CARP, CATLA CATLA (HAM-BUCH) - BAL, RUPALI; DUA, ANISH (Journal of the Inland Fisheries Society of India, 2021)
Numerous miniature configuration details, hidden on fish scale surface are of significance for fish identification, classification and taxonomy (Agassiz, 1834; Goodrich, 1908; Chu, 1935; Matsui, 1949; Kobayashi, 1951). The advent of techniques like Scanning Electron Microscopy (SEM) and utilization of its magnifying potencies for unfolding the architectural details of scale has been practiced by several eminent fish biologists to correlate this important aspect of scale morphology to fish taxonomy (DeLamater and Courtenay, 1972; DeLamater and Courtenay, 1973a, b, 1974; Lanzing and Higginbotham, 1974; DiCenzo and Sellers, 1998; Johal and Thomas, 2000; Ruiqing et al., 2000; Gao et al., 2001; Khemiri et al., 2001). The growing utilitarian aspect of the scale and its morphology thus makes it mandatory to elaborate the embedded morphoprints of scale to fit the relevant data better into the problem related to the field of fisheries. So realizing the significance of this aspect of scale structure, present study has been conducted to assess detailed scale structure of Catla catla using SEM technique.